APPLICATION OF INQUIRY LEARNING MODEL TO IMPROVE IPAS CLASS IV LEARNING OUTCOMES AT SD NEGERI 59 LUBUKLINGGAU - Apriliani (CV Grasta Glory, 2025)
This study aims to analyse the effectiveness of the application of the inquiry learning model in improving student learning outcomes in IPAS (Integrated Natural and Social Sciences) for fourth-grade students at SD Negeri 59 Lubuklinggau. This research is motivated by the low learning outcomes and limited student engagement in IPAS classes, which are still dominated by conventional teaching methods and lack of exploratory learning activities. The study employed a quasi-experimental method using a one-group pretest-posttest design, in which students were first given a pretest, followed by learning sessions using the inquiry model, and concluded with a posttest. The results showed a significant improvement in learning outcomes, indicated by the increase in average scores from 44.70 in the pre-test to 83.05 in the post-test. The number of students achieving mastery also increased, going from 0 to 18. A statistical Z-test revealed Z_cal = 6.94 > Z_table = 1.64, which confirms the acceptance of the research hypothesis. These findings demonstrate that the inquiry learning model has a positive and significant impact on student achievement. We conclude that the inquiry model effectively enhances IPAS learning outcomes among elementary students. Practically, the study suggests that educators should consider implementing inquiry-based strategies to foster student curiosity and engagement. For future research, it is recommended to explore the integration of inquiry learning with digital tools or to investigate its impact across different grade levels and subjects.